Two sides of the same coin : Nihonjinron and native-speakerism in a Japanese lower secondary school English language textbook - Shirahata, Mai (2018)
More and more scholars have been advocating the intercultural approach to language education, which is based on plurilingualism, pluriculturalism, and interculturalism. However, in the Japanese school context there are ideological impediments to this approach: nihonjinron and native-speakerism. Nihonjinron is an attempt to construct a cultural and national identity of the Japanese; native-speakerism is linguistic stereotyping, which gives privileges to certain speakers of a particular language over other speakers. The aim of this study is to illustrate how nihonjinron and native-speakerism are reconstructed through stereotypical portrayals of people in different nationality/ethnic groups within a Japan’s lower secondary school English language textbook. Images and texts in the chosen textbook were analyzed with the use of Critical Discourse Analysis. This study revealed that: People with particular characteristics consistent with nihonjinron and native-speakerism appeared in the textbook; the ingroup/outgroup status of a nationality/ethnic group in the textbook was consistent with the status of the group in terms of nihonjinron and native-speakerism; nihonjinron and native-speakerism coexisted in the textbook. The findings indicate that nihonjinron and native-speakerism were sophisticatedly reconstructed within the textbook by selecting particular nationality/ethnic groups to appear and depicting them in particular ways. Furthermore, it is implied that native-speakerism may have been reinforcing nihonjinron in the textbook. This study suggests that school English teachers in Japan should critically look at cultural stereotypes embedded in textbooks for practicing intercultural language teaching in their classrooms.